Effectiveness of 13-valent pneumococcal conjugate vaccine against community acquired pneumonia among children in China, an observational cohort study. Issue 33 (30th July 2021) - Zhang, Tao; Zhang, Jun; Shao, Xuejun; Feng, Shuang; Xu, Xinxin; Zheng, Benfeng; Liu, Changpeng; Dai, Zirui; Jiang, Qin; Gessner, Bradford D.; Chen, Qinghui; Zhu, Jun; et al.
Abstract: Background: In China, 13-valent pneumococcal conjugate vaccine (PCV13) has been available since 2017, but only via the private market with low uptake rate. We assessed the direct effectiveness of PCV13 against community acquired pneumonia (CAP) associated with PCV13 serotype carriage (VT-CAP). Methods: We conducted an observational cohort study of children born during 12-Dec-2016 to 30-Nov-2018 identified in the Suzhou Centers for Disease Control vaccine registry database, and who had at least one inpatient or outpatient record at the Suzhou University Affiliated Children's hospital (SCH) health-information-system (HIS) database. The vaccine registry cohort was followed through the HIS database through 30-Jun-2019 to identify hospitalized VT-CAP. Pneumococci were isolated from deep upper respiratory aspirates and serotyped with Quellung reactions. Results: We included 139, 127 children of whom 9024 (6.5%) received 1 + PCV13 doses (95.8% received 2 + doses). Within the total cohort, we identified 548 children hospitalized at SCH for VT-CAP, of whom 10 had received 2 + PCV13 doses. Adjusted for demographics, receipt of other childhood vaccines, and underlying medical conditions, the first visit vaccine effectiveness among children who had received 2 + PCV13 doses was 60.9% (95% CI: 25.8% to 79.4%) for VT-CAP and 17.9% (95% CI: 5.5% to 28.6%) for clinical CAP. Incidence rate reductions per 100, 000 child-years of observation for all visits were 208 (95% CI: 118 to 298) for VT-CAP and 720 (95% CI: 304 to 1135) for clinical CAP. Conclusions: PCV13 was protective against hospitalized VT-CAP and clinical CAP with large associated incidence rate reductions among children living in Suzhou, China.